Hubungan Antara Perilaku Kewargaan Organisasional Dan Kinerja Tugas - D. Wahyu Ariani (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2011)
The main purpose of this study is to find out relationship between organizational citizenship behavior and task performance in banking industries in Indonesia. Organizational citizenship behavior is composed of four components: altruism, civic virtue, and sportsmanship. To analyzed results mean, standard deviation, and correlation analysis techniques are used. 636 questionnaires were received and response rate 95 percent. Results prove that organizational citizenship behaviors do not have positive relationship with task performance.